2021
DOI: 10.1111/coep.12519
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between in‐person voting and COVID‐19: Evidence from the Wisconsin primary

Abstract: On April 7, 2020, Wisconsin held its presidential primary election, and news reports showed long lines of voters due to fewer polling locations. We use county‐level variation in voting patterns and weekly county‐level COVID test data to examine whether in‐person voting increased COVID‐19 cases. We find a statistically significant association between in‐person voting density and the spread of COVID‐19 2–3 weeks after the election. In our main results, a 10% increase in in‐person voters per polling location is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…The general belief that the virus is not real and the safety measures are not required could mean that COVID-19 may not reduce inperson voter turnout in Nigeria, contrary to the finding that it reduced turnout in the US primary elections (Flanders et al 2020;Morris and Miller 2020). However, this may lead to an increase in the number of COVID-19 cases, as Cotti et al (2020) argued, and perhaps increased casualties for the aged population (Bertoli et al 2020) because age increases the odds of voting, as this study's results indicate. Thus, in this scenario, increasing absentee voting may be encouraged as many voters shift to a more health-preserving means of voting (Yoder et al 2020).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The general belief that the virus is not real and the safety measures are not required could mean that COVID-19 may not reduce inperson voter turnout in Nigeria, contrary to the finding that it reduced turnout in the US primary elections (Flanders et al 2020;Morris and Miller 2020). However, this may lead to an increase in the number of COVID-19 cases, as Cotti et al (2020) argued, and perhaps increased casualties for the aged population (Bertoli et al 2020) because age increases the odds of voting, as this study's results indicate. Thus, in this scenario, increasing absentee voting may be encouraged as many voters shift to a more health-preserving means of voting (Yoder et al 2020).…”
Section: Discussionmentioning
confidence: 94%
“…The research exploring the relationships between COVID-19 and electoral outcomes is still very nascent and absent in Africa and many other developing countries and regions. Most of the few studies that have been done were conducted in the US (Cotti et al 2020;Flanders et al 2020;Morris and Miller 2020), except a very few studies done in France (Bertoli et al 2020;Cassan and Sangnier 2020). The thrust of the existing studies has been on determining whether turnout during the pandemic increased the risk of more cases (Cotti et al 2020;Flanders et al 2020) or deaths from COVID-19 (Bertoli et al 2020;Cassan and Sangnier 2020).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Among several studies documenting "superspreading" events due to large public gatherings, [13][14][15] some studies have suggested that elections may also be linked to increased viral transmission 16,17 ; however, evidence on these surges has been mixed. 18 Nevertheless, in 2020 state governments implemented election delays and varying changes to voting processes for statewide and national elections, such as mailing ballots or ballot applications to voters and temporarily switching to universal mail-in voting.…”
Section: Introductionmentioning
confidence: 99%